2016
DOI: 10.1103/physrevlett.117.114101
|View full text |Cite|
|
Sign up to set email alerts
|

Symmetric States Requiring System Asymmetry

Abstract: Spontaneous synchronization has long served as a paradigm for behavioral uniformity that can emerge from interactions in complex systems. When the interacting entities are identical and their coupling patterns are also identical, the complete synchronization of the entire network is the state inheriting the system symmetry. As in other systems subject to symmetry breaking, such symmetric states are not always stable. Here we report on the discovery of the converse of symmetry breaking-the scenario in which com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…In particular, the synchronizability of almost any symmetry cluster can be enhanced precisely by breaking the internal structural symmetry of the cluster. These findings add an important new dimension to the recent discovery of parametric asymmetry-induced synchronization [18][19][20], a scenario in which the synchronization of identically coupled identical oscillators is enhanced by assigning nonidentical parameters to the oscillators. Here, we show that synchronization of identically coupled identical oscillators is enhanced by changing the connection patterns of the oscillators to be nonidentical.…”
mentioning
confidence: 68%
“…In particular, the synchronizability of almost any symmetry cluster can be enhanced precisely by breaking the internal structural symmetry of the cluster. These findings add an important new dimension to the recent discovery of parametric asymmetry-induced synchronization [18][19][20], a scenario in which the synchronization of identically coupled identical oscillators is enhanced by assigning nonidentical parameters to the oscillators. Here, we show that synchronization of identically coupled identical oscillators is enhanced by changing the connection patterns of the oscillators to be nonidentical.…”
mentioning
confidence: 68%
“…The relationship between symmetry and synchronization underlies many recent discoveries in network dynamics. Symmetries influence the possible dynamical patterns in a network [1,2], and can either facilitate [3][4][5] or inhibit [6][7][8] synchronization. A particularly interesting symmetry phenomenon in networks is the coexistence of coherent and incoherent clusters in populations of identically coupled identical oscillators [9,10]-the so-called chimera states [11].…”
Section: Introductionmentioning
confidence: 99%
“…3 For example, in some applications, the interface between AC generators and the grid in wind-turbine systems is an MC. In general, an object has symmetry if it looks the same from different viewpoints 16 ; it is the property of being well balanced. 5 Recent matrix converters studies on dynamical models are reported in Kordonis and Hikihara 6 ; circuit topologies in Trentin et al, 7 Liu et al, 8 and Mizutani et al 9 Furthermore, Siami et al 10 At the boundary of straightforward research, unexpected behavior is disregarded without actually going into an in-depth analysis of the cause.…”
Section: Introductionmentioning
confidence: 99%
“…This paper analyzes the behavior of a MC under unbalanced (asymmetric) loads conditions. In general, an object has symmetry if it looks the same from different viewpoints 16 ; it is the property of being well balanced. 17 Symmetry has been part of human culture in the form of arts and science, with its first mathematical foundations presented in 1830.…”
Section: Introductionmentioning
confidence: 99%